Assessment of Ground Water Quality in and around Gobichettipalayam Town Erode District, Tamilnadu. Issue 3 (2007) - Palanisamy, P. N.; Geetha, A.; Sujatha, M.; Sivakumar, P.; Karunakaran, K.
Abstract : Ground water samples collected from different localities in and around Gobichettipalayam town, Erode District, Tamil Nadu were analyzed for their physico- chemical characteristics. This analysis result was compared with the WHO & ICMR standards of drinking water quality parameters with the following water quality parameters namely pH, Electrical conductivity, CN -, Cl -, SO4 2-, Na +, K +, Ca & Mg in CaCO3 equivalents, phenolphthalein alkalinity, hydroxide alkalinity, carbonate alkalinity, bicarbonate alkalinity, total alkalinity, total dissolved solids, total solids, total suspended solids, calcium, magnesium, total hardness, dissolved oxygen, fluoride etc ., The usefulness of these parameters in predicting ground water quality characteristics were discussed. Thus an attempt has been made to find the quality of ground water in and around Gobichettipalayam town, suitable for drinking purposes or not.